Substitution in Markusen’s Classic Trade and Factor Movement Complementarity Models - Schiff, Maurice (World Bank, Washington, DC, 2012)
Mundell and Markusen each wrote classic papers on the relationship between trade and factor movement. Mundell showed that substitution holds in the Heckscher-Ohlin model. Markusen challenged the substitution result and showed in five different models that removing barriers to factor movement results in complementarity under free trade, identical factor endowments, and a change in any one of the other assumptions underlying the Heckscher-Ohlin model. The author generalizes Markusen's analysis by considering the liberalization of barriers to factor movement under any non-negative level of protection, and liberalizing trade barriers under factor mobility. He shows that (1) substitution holds at high protection levels, (2) complementarity holds at low protection levels, and (3) either substitution or complementarity hold under large tariff changes.